Comparative analysis of landscape effects on spatial genetic structure of the big brown bat and one of its cimicid ectoparasites. Issue 20 (6th September 2017) - Talbot, Benoit; Vonhof, Maarten J.; Broders, Hugh G.; Fenton, Brock; Keyghobadi, Nusha
Abstract: Identification of landscape features that correlate with genetic structure permits understanding of factors that may influence gene flow in a species. Comparing effects of the landscape on a parasite and host provides potential insights into parasite‐host ecology. We compared fine‐scale spatial genetic structure between big brown bats ( Eptesicus fuscus ) and their cimicid ectoparasite ( Cimex adjunctus ; class Insecta) in the lower Great Lakes region of the United States, in an area of about 160, 000 km 2 . We genotyped 142 big brown bat and 55 C. adjunctus samples at eight and seven microsatellite loci, respectively, and inferred effects of various types of land cover on the genetic structure of each species. We found significant associations between several land cover types and genetic distance in both species, although different land cover types were influential in each. Our results suggest that even in a parasite that is almost entirely reliant on its hosts for dispersal, land cover can affect gene flow differently than in the hosts, depending on key ecological aspects of both species. Abstract : The aim of this paper was to investigate the effect of landscape composition on the spatial genetic structure of the big brown bat and one of its cimicid ectoparasites, Cimex adjunctus, in the North American Great Lakes region. Previous findings in the literature suggest dispersal and gene flow are correlated between parasites and hosts, but several factors have been identified that may affect the strength of this correlation. In our paper, we suggest landscape composition may also influence dispersal and gene flow differently in a parasite and a host, depending on the location and timing of gene flow events in each species.